Effect of immersion time on the combustion characteristics of oil‐impregnated transformer insulating paperboard. (22nd July 2022) - Zhang, Jiaqing; Guo, Yi; Yang, Tianqi; Chen, Qingtao; Luo, Chao
Abstract: Transformer insulating paperboard is an insulating material commonly used in the oil‐filled equipment in substations, which is usually immersed in the transformer oil. In this study, the effects of immersion time on the combustion characteristics of oil‐impregnated transformer insulating paperboard are studied using the thermogravimetric, UL94 vertical flammability, and cone calorimeter experiments. The experimental results show that the total oil content increases with increasing immersion time and reaches the saturation state in 240 h, with a saturation content of 14.7% ± 0.5%. However, the distribution of oil content inside the paperboard is uneven. At the saturation state, the surface oil content is 35.5%, being about 3 times of the core oil content. The results of UL94 vertical flammability experiments show that the flame spread rate increases with increasing immersion time and is controlled by the total oil content. In the cone calorimeter experiments, the time to ignition is significantly reduced compared to the clean paperboard. Unlike the flame spread rate, the ignition time is controlled by the surface oil content and barely varies with immersion time. The critical heat flux of oil‐impregnated transformer insulating paperboard is found as 3.9 kW/m 2, being only 1/3 of clean paperboard. With increasing immersion time, the peak heat release rate increases, while the total heat release, fire growth index, and effective heat of combustion present linear correlations with the total oil content. The CO yield increases with increasing immersion time, and the released CO mainly comes from the combustion of transformer oil.